Clearance of Parental Products - Svoboda, Petr; Fulka, Helena; Malik, Radek (Advances in experimental medicine and biology, 2017)
The beginning of development is controlled parentally. For example, early zygotic proteosynthesis produces proteins encoded by the maternal transcriptome. As parental factors become replaced by factors synthesized in the embryo, parental developmental control is gradually passed to the embryo. This chapter focuses on the clearance of parental factors during oocyte-to-embryo transition in vertebrates. Coordinated removal of parental factors erases ancestral oocyte identity of the zygote and facilitates reprogramming of gene expression into a state that will support development of a new organism. Here, we will review functional and mechanistic aspects of clearance of selected parental factors from early embryos, including different types of maternal RNAs, proteins, erasure of chromatin features of maternal and paternal genomes, as well as consumption of yolk and elimination of paternal mitochondria.
Keywords: Animals; Fertilization; Embryo, Mammalian; Proteasome; Gene Expression Regulation, Developmental; Oocyte; Chromatin; Zygote; Oocytes; zygota; Zygotic; mRNA degradation; oocyty; Protein degradation; chromatin; Maternal; transkriptom; Reprogramming; zvířata; Transcriptome; vývojová regulace genové exprese; embryo savčí